WOW – a multilayered reflection on collective movements - Deres, Andrea; Bäckman, Carolina; Vestreim, Ellesiv S.; Karlsson, Sofia; Bigas Bassart, Quim (Peripeti, 2020)
Through a collective writing five dance artists share their individual and common experiences of collective, weaving together an intricate body of text. A playful and sincere approach towards different collective settings, modes and textures, exploring the rich complexity of being many in one – what it can entail, unfold and generate